Anestesi Epidural Thorakal pada Operasi Shapp Plate pada Pasien dengan Fraktur Kosta Tertutup Multipel - Fardian, Dedy; Laksono, Ristiawan Muji (Majalah Anestesia dan Critical Care, 2014)
Teknik anestesi epidural thorakal banyak digunakan dengan atau tanpa anestesi umum pada operasi daerahthoraks, abdomen dan retroperitoneal. Penggunaan kombinasi dengan anestesi umum akan mengurangi kedalamananestesi dan hemodinamik lebih stabil, serta pulih lebih cepat. Laporan kasus ini, wanita usia 65 tahun, dengandiagnosis fraktur tertutup costae 3–7 sebelah kanan yang menjalani operasi SHAPP klipping kosta dengan anestesiumum dikombinasi epidural thorakal. Status isik pasien ASA 3 dengan geriatri, hipertensi terkontrol, iskemiaanteroekstensif. Anestesi epidural dengan pendekatan median setinggi vertebra T7-8, teknik loss of resistance padakedalaman 3,5 cm dan kateter sedalam 5 cm. Setelah test dose negatif, dilakukan intubasi endotrakeal. Bupivakain0,25% 8 mL+fentanil 50 μg didiberikan ke dalam kateter epidural. Operasi berlangsung stabil dengan tingkatsedasi ringan anestesi inhalasi. Penatalaksanaan nyeri pascaoperasi dengan bupivakain 0,125%+morin 1 mg totalvolume 8 mL, VAS score 0–1. Pada hari ke-4, kateter epidural dicabut diganti obat NSAID oral. Pasien dipulangkanpada hari ke-5. Anestesi epidural thorakal merupakan teknik anestesi yang mempunyai beberapa kelebihan efekanalgesianya, efek perubahan hemodinamik minimal serta menurunkan risiko komplikasi pascaoperasi sehingga berperan utama dalam anestesi bedah thoraks pada geriatri termasuk penatalaksanaan nyeri pascaoperasinya. Kata kunci: Anestesi epidural thorakal, geriatri, hemodinamik stabil, komplikasi pascaoperasi, penatalaksanaan nyeri pascaoperasi Thoracic epidural anesthesia has become widely used with or without general anesthesia for thoracic, abdominal,and retroperitoneal procedures. Combined with general anesthesia, it decreases the need for deep level of anesthesiaand provides more hemodynamically stable operative course and faster emergence of general anesthesia. In thiscase report, an elderly woman, 64 years old, suffered from right 3rd–7th closed rib fracture undergo SHAPP clippingrib surgery under general anesthesia combined with thoracic epidural anesthesia. The physical status was ASA 3with geriatric, controlled hypertension, anteroextensive ischemia. Epidural anesthesia was performed with medianapproach in level T7-8, loss of resistance technique had been used to ind epidural space at 3.5 cm depth, and 5cm catheter was inserted. After the test dose showed negative result, the endotracheal intubation was performed.Bupivacaine 0.25% 8 mL+fentanyl 50 μg was injected intra epidural catheter. The operation went stable with lowlevel sedation of inhalation anesthetics agent. For post operative pain management we used regimen bupivacaine0.125%+morphine 1 mg total volume 8 mL, VAS score 0–1. On the day 4 after surgery, the epidural catheter wasremoved and switched to oral NSAID and the patient discharged on day 5. Thoracic epidural anesthesia is oneof regional anesthesia technique with many advantages such as superiority of pain relief, minimally changes inhemodynamic also lowering risk of postoperative complication, so it plays a major role providing anesthesia inthoracic surgery especially in geriatric, including post operative pain management.Key words: Geriatric, hemodynamically stable, post operative complication, post operative pain management, thoracic epidural anesthesia Reference Yilmaz M, Wong CA. Technique of neuraxial anesthesia. Dalam: Wong CA, penyunting. Spinal and Epidural Anesthesia. New York: McGraw-Hill, Inc; 2007. hlm. 56–9. Hadzic A. Epidural blockade. Dalam: Hadzic A, penyunting. Textbook of regional anesthesia and acute pain management. New York: McGraw-Hill; 2007. hlm. 253–56, 267–70. Brown, DL. Spinal, epidural and caudal anesthesia. Dalam: Miller RD, penyunting. Miller’s Anesthesia. Edisi ke-7. Philadelphia: Churcill Livingstone; 2009. hlm.1611–38, 2261–76. Xie Z, Lanahan J. Anesthesia for geriatric patients. Dalam: Dunn, PF, penyunting. Clinical anesthesia procedures of the massachusetts general hospital. Edisi ke-7. Philadelphia: Lippincott Williams and wilkins; 2007.hlm. 487–91. Akhtar S. Ischemic heart disease. Dalam: Stoelting’s Anesthesia and co-existing disease. Edisi ke-5. Philadelphia: Churcill livingstone; 2009. hlm.11–20. Wu CL, Hurley RW. Post operative pain management and patient outcome. Dalam: Post operative pain management: an evidencebased guide to practice. Philadelphia: Saunders; 2006. hlm. 50, 75–9. Strebel BM, Ross S. Chronic postthoracotomy pain syndrome. CMAJ 2007177: 1029. Macrae WA. Chronic post-surgical pain: 10 years on. Br J Anaesth. 2008;101:77–86. Gerner P. Post-thoracotomy pain management problems. Anesthesiol Clin. 2008;26(2):355. Sokouti M, Aghdam BA, Golzari SEJ, Moghadaszadeh M. A comparative study of post operative pulmonary complications using fast track regimen and conservative analgesic treatment: a randomized clinicaltrial. Tanaffos 2011;10(3):12–9 Kettner SC , Willschke H, Marhofer P. Does regional anaesthesia really improve outcome? Br J of Anaesth. 2011;107(S1):i90–5.